Contemporary Definitions of Suicidal Behavior: A Systematic Literature Review. Issue 2 (24th March 2018) - Goodfellow, Benjamin; Kõlves, Kairi; de Leo, Diego
Abstract : To address the lack of comparability around the world, we conducted a systematic review of existing definitions of suicide and suicidal behaviors. In the literature, four key features appear to cover the vast majority of concepts underpinning definitions: agency, knowledge of a potential fatal outcome, intent, and outcome. Intent and outcome appear to be the most consensual features of definitions of suicide, albeit revealing interesting conceptual variations. The four key features could be used to devise a research tool able to explore the meanings of suicide across different countries and different cultures.